The weight of nineteenth century Mexicans in the Western United States. Issue 1 (2nd January 2018) - Carson, Scott Alan
ABSTRACT: When traditional methods for measuring economic welfare are scarce or unreliable, heights and BMIs are now well-accepted measurements that represent biological conditions during economic development. Weight, after controlling for height, is an additional measure for current net nutrition. Little is known about how weights varied among Mexicans living in the nineteenth century American West. Between 1870 and 1920, average Mexican weight was low and remained constant. Mexican farmers had the heaviest weights, and unskilled worker weights were low. Weight of Mexican-born individuals were higher than Mexicans born in the United States at low weights but lower at high weights. For combined characteristics, weight varied the most with age, an uncontrollable characteristic, indicating that nineteenth century Mexican current net nutrition varied the most with factors over which they had no control.